Analisa Skedul Proyek Pengadaan dan Pemasangan High Pressure Heater PLTU dengan Metode Earned Value Analysis di PT. X - Tiara Belen Rante Tadung; Iriani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT. X is a strategic enterprise focusing on the production of the main equipment of the country's defense system, especially in the marine field. One of the company's business lines includes shipbuilding and non-ship projects, such as the procurement and installation of HPH 3 Unit 2 at coal-fired power plants. Based on the importance of schedule planning or project management in the company, a project scheduling analysis was carried out on the procurement and installation sub-work of HPH 3 Unit 2 PLTU using the Earned Value Analysis (EVA) method, which is an approach in project management to make it easier to control time and costs. The data used in this study are Master Schedule, and S-Curve. The results of the analysis show that the estimated time remaining (ETS) is 499 days, with a projected total project completion time (EAS) of 626 days. In the S-Curve chart, the actual progress of the project is seen in line with the planning graph. In addition, the value of BCWP (Budgeted Cost of Work Performed) is mostly greater than that of BCWS (Budgeted Cost of Work Scheduled), which indicates the acceleration of project progress compared to the planned schedule.